Toxic/Bioactive Peptide Synthesis Genes Rearranged by Insertion Sequence Elements Among the Bloom-Forming Cyanobacteria Planktothrix - Entfellner, Elisabeth; Li, Ruibao; Jiang, Yiming; Ru, Jinlong; Blom, Jochen; Deng, Li; Kurmayer, Rainer (Frontiers in Microbiology, 2022)
It has been generally hypothesized that mobile elements can induce genomic rearrangements and influence the distribution and functionality of toxic/bioactive peptide synthesis pathways in microbes. In this study, we performed in depth genomic analysis by completing the genomes of 13 phylogenetically diverse strains of the bloom-forming freshwater cyanobacteria Planktothrix spp. to investigate the role of IS elements in seven pathways. Chromosome size varied from 4.7–4.8 Mbp (phylogenetic Lineage 1 of P. agardhii/P. rubescens thriving in shallow waterbodies) to 5.4–5.6 Mbp (Lineage 2 of P. agardhii/P. rubescens thriving in deeper physically stratified lakes and reservoirs) and 6.3-6.6 Mbp (Lineage 3, P. pseudagardhii/P. tepida including planktic and benthic ecotypes). Although the variation in chromosome size was positively related to the proportion of IS elements (1.1–3.7% on chromosome), quantitatively, IS elements and other paralogs only had a minor share in chromosome size variation. Thus, the major part of genomic variation must have resulted from gene loss processes (ancestor of Lineages 1 and 2) and Horizontal Gene Transfer (HGT). Six of seven peptide synthesis gene clusters occurred already in the ancestor of P. agardhii/P. rubescens, and became partly lost during the evolution of Lineage 1. Six of seven peptide synthesis gene clusters were found located on the chromosome. In general, no increased IS element frequency in the vicinity of peptide synthesis gene clusters was observed. We found a higher proportion of IS elements in ten breaking regions related to chromosomal rearrangements and a tendency for colocalization of toxic/bioactive peptide synthesis gene clusters on the chromosome.